1982
DOI: 10.1111/j.1365-2389.1982.tb01751.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal fluctuations in nitrogen fixation (acetylene reduction) by free‐living bacteria in soils contaminated with cadmium, lead and zinc

Abstract: Acetylene reduction by non-symbiotic, heterotrophic micro-organisms in a range of soils containing different concentrations of heavy metals was determined using intact soil cores. The suitability of this method for the soils used in this investigation was established. Samples were collected seasonally, and were incubated under standard conditions (darkness: 15%). Mean values of metal concentrations in the soil (pg g-I)were: Cd: 1-200; Pb: 60-8000; Zn: 70-26000, Cu: 20-40. Rates of acetylene reduction were gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Copper, even at very low concentrations (5 pg l ' ) , has been shown to eliminate nitrogen fixation by cyanobacteria after 3 d of exposure (Horne and Goldman, 1974). However, another study found no correlation between concentrations of Cd, Pb, Zn, and Cu in soils and acetylene reduction activity (Rother et al, 1982). Sewage sludge (with high metal content) decreases the denitrification potential of a saltmarsh and this effect is attributed to some toxic component of the sludge (Sherr and Payne, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Copper, even at very low concentrations (5 pg l ' ) , has been shown to eliminate nitrogen fixation by cyanobacteria after 3 d of exposure (Horne and Goldman, 1974). However, another study found no correlation between concentrations of Cd, Pb, Zn, and Cu in soils and acetylene reduction activity (Rother et al, 1982). Sewage sludge (with high metal content) decreases the denitrification potential of a saltmarsh and this effect is attributed to some toxic component of the sludge (Sherr and Payne, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…To a large extent, only one population of white clover (T. repens) was identified to have conserved a potential for nitrogen fixation on soil highly contaminated with Zn i.e. containing up to 30,000 mg Pb kg -1 soil and 20,000 mg Zn kg -1 soil (Rother et al 1982).…”
Section: Rhizobium Survival In Heavy Metal-contaminated Soilmentioning
confidence: 99%
“…Therefore, examples showing symbiotic associations conserving their ability to fix N on highly contaminated soils are scarce (Giller et al 2009). A white clover (Trifolium repens) population was identified on soil containing up to 20,000 mg Zn kg -1 soil and 30,000 mg Pb kg -1 soil (Rother et al 1982), and more recently symbiotically effective Sinorhizobium meliloti strains tolerant to As, Cu and Pb were found in soils contaminated after the toxic spill at the Aznalcollar pyrite mine (Carrasco et al 2005). Freeliving bacteria were isolated from mine tailings and Cupriavidus (formerly Wautersia/Ralstonia) metallidurans was described as a model metal-tolerant bacterium (Mergeay et al 2003;Vaneechoutte et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, reduction of litter mass in the first stage of decomposition has been assigned to be unaffected by 1000 mg kg -1 Pb not only in the present paper but also in the past (Crist et al 1985). Even higher lead levels may not prevent microbial communities maintaining important ecophysiological processes in soil, for example, nitrogen fixation or acetylene reduction (Rother et al 1982). In single cases, fungi have been found to be tolerant to 10 000 mg kg -1 Cd (Tatsuyama et al 1975).…”
Section: Discussionmentioning
confidence: 92%